Mental health disparities amongst sexual-minority adolescents of the US – A national survey study of YRBSS-CDC. (August 2022) - Depa, Nishitha; Desai, Saral; Patel, Shweta; Silvi, Suraiya; Hanif, Sarah; Rizvi, Syeda; Rahman, Fayaz; Ortega, Gizelle; Hsieh, Ya-Ching; Malik, Preeti; Pathrose, Rana Prathap Mercy; Parikh, Tapan; et al.
Highlights: It is important to evaluate the prevalence trends of suicidal behaviors among sexual minority youth, compared to their heterosexual peers and risk factors leading to suicidality in this population. In our retrospective cross-sectional study using YRBSS data from 2015-2019, sexual minority had higher odds of feeling sad and hopeless (aOR:4.6; 95%CI:4.0-5.2; p<0.0001), considering suicide (3.2; 2.8-3.7; p<0.0001), planning suicide (2.0; 1.7-2.3; p<0.0001) compared to heterosexual. Amongst sexual minority, prevalence of substance abuse like cigarette, cocaine, marijuana, heroin and injectable drugs were higher compared to heterosexual. We conclude that sexual minority adolescents are at higher risk of substance abuse, depression and suicidality compared to heterosexual peers. Abstract: Objective: We aimed to evaluate the prevalence and trend of identifying as a sexual minority among the American adolescent population. Additionally, we aimed to evaluate the prevalence and odds of substance abuse, hopelessness, and suicidality among the sexual minority adolescents compared to their heterosexual peers. Methods: We performed a retrospective cross-sectional study using Youth Risk Behavior Surveillance System (YRBSS) data from 2015 to 2019. YRBSS divides "Sexual identity" into three groups: heterosexuals, sexual minorities (gay or lesbian or bisexual), and unsure. We identified "hopelessness and suicidality" using the survey questions exploring if participants felt sad or hopeless for >2 weeks, considered suicide, made a suicide plan, and attempted suicide requiring medical care. Univariate and multivariable survey logistic regression analyses were performed to establish an association between hopelessness, suicidality, substance abuse, and identifying as a sexual minority. Results: Out of 41, 377 adolescents, 4055 (9.8%) identified as a sexual minority. An increasing percentage of adolescents identified themselves as a sexual minority between 2015 to 2019 (8% to 11.2%) (pTrend<0.0001). The sexual minority had a higher prevalence of feeling sad and hopeless (63.4 vs. 28.6%), considering suicide (46 vs. 14.2%), planning suicide (38.9 vs. 11.5%), attempting suicide, and having injurious suicide attempts compared to heterosexuals. (p<0.0001) Amongst sexual minorities, the prevalence of substance abuse was higher compared to their heterosexual peers, which includes cigarettes (15 vs 7.8%), e-cigarette (27.2 vs 23.2%), inhalants (14.1 vs 5.3%), cocaine (8.4 vs 3.9%), marijuana (31.2 vs 20.2%), alcohol (36.9 vs 30.3%), steroids (6.4 vs 2.2%), heroin (4.4 vs 1.2%), and injectable drugs (4.0 vs 1.1%) (p<0.0001). In regression analysis, the sexual minority had higher odds of substance abuse, feeling sad and hopeless (aOR:4.6; 95%CI:4.0-5.2; p<0.0001), considering suicide (3.2; 2.8-3.7; p<0.0001), planning suicide (2.0; 1.7-2.3; p<0.0001) compared to heterosexual. Conclusion: Sexual minorities not only have higher prevalence and odds of hopelessness and suicidality but also have higher prevalence and odds of substance abuse like cigarettes, marijuana, cocaine, heroin, inhalants, and steroids. Hence, early identification, risk stratification, and interventions to reduce mental health disparities are needed.